The Effectiveness of Panel Discussion on Senior High School Students' Speaking Skills - Vickry, Fachreza Aprileo; Laeli, Anita Fatimatul; Nuraini, Kristi (International Journal of English Education and Linguistics (IJoEEL), 2024)
This research aims to determine the effect of panel discussion on the speaking skills of 2nd-grade senior high school students. This research employed a quantitative method using a quasi-experimental design, where the subjects were not randomly assigned to the treatment group. The instrument used to collect data for this research was a rubric focusing on criteria such as content, fluency, pronunciation, vocabulary, and grammar, which scores the students' speaking skills based on the speaking test. The researcher used a subjective test to measure the students' speaking skills in this test. In the control group (XI-9), pre-test scores ranged from 40 to 68, with a mean of 50.86, and post-test scores ranged from 40 to 72, with a mean of 57.49. In the experimental group (XI-10), pre-test scores ranged from 40 to 76, with a mean of 55.43, and post-test scores ranged from 40 to 84, with a mean of 70.60. The results indicated that panel discussion significantly improved students' speaking skills. For future research, it is suggested that more of the scope sample be explored and that the research be longer than this one to get a more comprehensive result. In addition, more research must be done to advance the impact of the panel discussion on other English skills.